Innovative use of tourniquet in the management of an advanced abdominal pregnancy to achieve an unusually normal postoperative outcome: a case report - Inyang Etoh, Emmanuel C.; Ettete, Iniobong E.; Adeneye, Christian A.; Inwang, Imaobong O.; Umoh, Augustine V. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Mrs. UVG was an un-booked G3P1+1 petty trader, who presented with an obstetric ultrasound scan report, with an incidental diagnosis of abdominal pregnancy at 32 weeks of gestation with the placenta attached to the fundus of the uterus. Her admission packed cell volume was 24%. She had pre-operative preparation and 2 units of compatible blood were transfused to correct the anemia. Four additional units of compatible blood were made available before she was scheduled for an exploratory laparotomy at 33 weeks of gestation. A grossly normal male infant weighing 2.2 kg was delivered from the peritoneal cavity with Apgar scores of 2 at 1 minute and the same at 5 minutes. The placenta which was attached to the fundus of the uterus was removed manually completely after a tourniquet had been applied distal to the point of separation. Intra-operative blood loss was 1000 ml. The infant died 1 hour after delivery due to respiratory failure. Autopsy report revealed massive intracerebral hemorrhage and pulmonary hypoplasia. The post-operative period was uneventful and the decline in serum assay of β-human chorionic gonadotrophin postpartum was normal. She was discharged home on the 8th post-operative day and seen at the postnatal clinic twice at weekly intervals with normal serum assay of β-human chorionic gonadotrophin. Her 6 weeks postnatal visit was also uneventful.